Do “say-on-pay” votes affect M&A decisions? - Dutta, Shantanu; Officer, Micah S.; Wang, Ruixiang; Zhu, Pengcheng (Journal of Corporate Finance, 2025)
This paper demonstrates that firms receiving above-industry-average support in their “say-on-pay” (SoP) votes engage in more M&A transactions in the subsequent year. Our empirical findings suggest that high levels of SoP voting support may boost managerial confidence, thereby stimulating increased pursuit of acquisitions. Moreover, we observe that managers garnering higher SoP vote support are more likely to secure shareholders' backing in M&A votes, receive higher compensation in successful deals, and face a reduced likelihood of forced turnover following unsuccessful deals. Additionally, we find that both short-term and long-term M&A performance significantly improves in deals announced by managers receiving higher SoP voting support. These findings contribute to our understanding of the relation between shareholder support for CEOs and firm investment.